DEVELOPMENT OF DAKON GAME INTERACTIVE E-BOOK MEDIA TO IMPROVE MATHEMATICS LEARNING OUTCOME OF ELEMENTARY SCHOOL STUDENTS - Maulidiyyah, Aisyah; Nafiah, Nafiah; Hartatik, Sri; Rahayu, Dewi Widiana (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2021)
The low student learning outcomes in the concept of learning addition and subtraction in learning Mathematics, especially for grade 1 in Elementary School, is still not optimal. This is one of the contributing factors is the lack of mathematics learning materials developed by the teachers, and not many teachers involve students in the learning process so that students are less active in responding to the ongoing Mathematics learning. This study is intended to design learning media that can improve student learning outcomes in learning Mathematics through the development of interactive e-book media for the Dakon game. The formulation of this problem is how is the process of developing the Dakon Game Interactive E-Book Media to Improve Mathematics Learning Outcomes of Elementary School Students and How is the feasibility of developing Dakon Game Interactive E-Book Media to Improve Mathematics Learning Outcomes of Elementary School Students, this study uses the R&D development method only at level 1 with the stages of collecting potentials and problems, literature study and information gathering, product design, design validation, and tested design. With the results of the linguist validation test, the percentage of eligibility of 85% was declared very feasible to use, then the material validation test with a feasibility percentage of 83% was also declared very feasible to use, and the last one was the empirical scale test with a feasibility percentage of 86% indicating that the e-book media Dakon student interactive game is very feasible to use.